On the origin of residual strain in shape memory alloys: experimental investigation on evolutions in the microstructure of CuAlBe during complex thermomechanical loadings. (24th January 2017) - Barati, M; Chirani, S Arbab; Kadkhodaei, M; Saint-Sulpice, L; Calloch, S
Abstract: The behaviors of shape memory alloys (SMAs) strongly depend on the presence of different phases: austenite, thermally-induced martensite and stress-induced martensite. Consequently, it is important to know the phase volume fraction of each phases and their evolution during thermomechanical loadings. In this work, a three-phase proportioning method based on electric resistivity variation of a CuAlBe SMA is proposed. Simple thermomechanical loadings (i. e. pseudoplasticity and pseudoelasticity), one-way shape memory effect, recovery stress, assisted two-way memory effect at different level of stress and cyclic pseudoelasticity tests are investigated. Based on the electric resistivity results, during each loading path, evolution of the microstructure is determined. The origin of residual strain observed during the considered thermomechanical loadings is discussed. A special attention is paid to two-way shape memory effect generated after considered cyclic loadings and its relation with the developed residual strain. These results permit to identify and to validate the macroscopic models of SMAs behaviors.